EXPLORATION OF THE LEVEL OF SCIENTIFIC INFORMATION LITERACY OF PALU CITY CLASS VII JUNIOR HIGH SCHOOL STUDENTS - Nur Rahmah; Lilies Tangge, Afadil (Adisam Publisher, 2024)
This research aims to explore the level of scientific information literacy of class VII junior high school students in two schools in Palu City. The era of globalization demands students' ability to navigate social media and digital information sources critically. The survey method was used by collecting data from 50 students using structured questionnaires and semi-structured interviews. Five dimensions of scientific information literacy are explored: information acquisition, information filtering, information credibility evaluation, information sharing, and opinion expression. The results showed that the majority of students demonstrated a high level of scientific information literacy, especially in information acquisition and filtering. However, the ability to evaluate the credibility of information and express opinions still requires further attention. These findings highlight the importance of developing students' critical skills in managing and assessing the information they encounter in digital environments. The educational implications of this research include the need for further integration of information literacy education in the school curriculum, with a focus on developing skills for evaluating the credibility of information sources and strengthening the ability to express opinions. Recommended strategies include intensive training for teachers in teaching information literacy, the use of technology to support learning, and the development of assessments that comprehensively reflect students' information literacy abilities. This research contributes to a deeper understanding of the status of students' scientific information literacy at the junior high school level, as well as providing a basis for the development of more effective educational strategies for facing the current challenges of information globalization.